Global inequality: Recent evidence and trends - Duangkamon Chotikapanich; D. S. Prasada Rao; William E. Griffiths; Vicar Valencia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper examines the nature and extent of global and regional income distribution and inequality using the most recent country level data on income distribution drawn from World Bank and UNU-WIDER studies for the period 1993-2000. The methodology used is a recently developed technique to fit flexible income distributions to limited aggregated data. Empirical results show a very high degree of global inequality, but with some evidence of inequality decreasing between the two years.
Keywords: C13; C16; D31; 330; Gini coefficient; beta-2 distribution; Einkommensverteilung; Gini-Koeffizient; Welt